Vulva Fibroadenoma Associated with Lactating Adenoma in a 26-Year-Old Nigerian Female - C. C. Anunobi; F. J. N. Obiajulu; A. A. F. Banjo; A. O. E. Okonkwo (Hindawi Limited, 2013)
Background. Vulva lactating adenoma is rare and may be misdiagnosed as adenocarcinoma in frozen section and aspiration cytology if breast tissue is not anticipated. Objective. To raise the awareness of lactating vulva ectopic breast lesion among clinicians and pathologists. Case Report. We present a case of vulva fibroadenoma associated with lactating adenoma in a 26-year-old Nigerian female. Conclusion. The rarity of vulva ectopic breast tissue can present a diagnostic challenge for both the clinician and the anatomical pathologist. Once excisional biopsy is done and the lesion confirmed histologically, the anxious patient can be reassured.